PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR BERBASIS DIGITAL UNTUK MENINGKATKAN PEMAHAMAN ANTI PERUNDUNGAN RELASIONAL PADA ANAK USIA DINI - Mahdavikia, Annisa; Reza, Muhammad; Rakhmawati, Nur Ika Sari; Fitri, Ruqoyyah (TARBAWI:Journal on Islamic Education, 2025)
The aim of this research is to determine the feasibility and effectiveness of the media that has developed to understanding of relational anti-bullying. Furthermore, this research uses a research and development (RD) research model with the ADDIE development procedure. The number of subjects used was 30 children in the age range of 5-6 years. The results of this research, the media was declared feasible and effective because received score from material experts of 95% and media experts of 93.75%. So, based on the score obtained from the Wilcoxon test with score of 0.001. It means the significance result is less than 0.05, then Ho is rejected and Ha is accepted, there is a difference of average results between pre-test and post-test. It concluded that the media developed is feasible and effective to use.